Case Report: A Pseudoaneurysm Involving the Left Common Iliac Artery Secondary to Brucellosis: A Rare Case Report - Wang, Qilong; Tang, Liang; Qin, Yue; Wang, Qi; Zhang, Ping; Cheng, Zhihua (Frontiers in Bioengineering and Biotechnology, 2021)
Pseudoaneurysms of the common iliac artery caused by Brucellosis are exceedingly uncommon. Infected common iliac artery pseudoaneurysms, particularly those caused by brucellosis, are more difficult to diagnose and cure than general pseudoaneurysms. The risk of mortality is significantly high in this condition. Nonsurgical treatment of a brucellosis-induced common iliac artery pseudoaneurysm is futile, and it should be operated on as soon as feasible. Long-term and multi-course antibacterial therapy with combination antibiotics is required. For the treatment of Brucella-infected pseudoaneurysms, endovascular surgery can be both effective and safe.